1997
DOI: 10.1161/01.hyp.29.3.706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of African-American Race and Hypertensive Left Ventricular Hypertrophy on Coronary Vascular Reactivity and Endothelial Function

Abstract: Excess cardiovascular morbidity and mortality among African (black) Americans remains an important yet unexplained public health problem. One possible explanation proposes that intrinsic or acquired abnormalities in coronary vascular reactivity and endothelial function result in excess ischemia among black Americans. To examine this hypothesis, we subjected 80 individuals with normal coronary arteries to invasive testing of coronary artery and microvascular relaxation using intracoronary infusions of acetylcho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 38 publications
4
21
0
1
Order By: Relevance
“…The findings of the current study may be more reliable because of our relatively large sample size and certainly suggest that not all black normotensive subjects have impaired vasodilator function. Notably, our findings are also consistent with work by Houghton and colleagues 22 demonstrating no racial differences in acetylcholine-mediated and adenosine-mediated dilation of coronary resistance vessels.…”
Section: Discussionsupporting
confidence: 93%
“…The findings of the current study may be more reliable because of our relatively large sample size and certainly suggest that not all black normotensive subjects have impaired vasodilator function. Notably, our findings are also consistent with work by Houghton and colleagues 22 demonstrating no racial differences in acetylcholine-mediated and adenosine-mediated dilation of coronary resistance vessels.…”
Section: Discussionsupporting
confidence: 93%
“…As previously reported in an interim publication, 19 we found no significant racial differences in conduit-and resistance-vessel vasoreactivity among normotensive subjects. The smaller number of normotensive study subjects (particularly among African Americans) reduces the statistical power of analyses in this subgroup, but the available data do not suggest racial differences in coronary vasoreactivity in normotensives.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, quality of measurement was previously shown to be consistent throughout the study period. 19 We acknowledge that angiographic assessment is insensitive for detection of atherosclerosis. However, patient groups such as ours with no angiographic CAD, yet endothelial dysfunction, are conjectured to represent an early stage in the natural history of CAD and/or cardiomyopathy, populations of enormous importance in preventive cardiology, where early diagnosis and individualized therapy might be especially efficacious.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…[86][87][88][89] In contrast to the studies performed in the forearm microvasculature, studies on coronary microvasculature resistance have shown that there are no racial differences between NTS AAs and NTS EAs in response to acetylcholine-induced (endotheliumdependent) or adenosine-induced (endothelium-independent) vasodilation. 87-89 Also, there are no differences in vascular reactivity to acetylcholine or adenosine between AA and EA women with chest pain, 86 although this study had a very small study population.…”
Section: Racial Differences In Vascular Reactivitymentioning
confidence: 94%